2021
DOI: 10.1016/j.celrep.2021.109845
|View full text |Cite
|
Sign up to set email alerts
|

Post-oral sensing of fat increases food intake and attenuates body weight defense

Abstract: Highlights d In mice, increasing percent calories from fat and sweetness increase diet palatability d Increasing fat content but not sweetness increases food intake and weight gain d Intragastric infusion of food dense in fat increases intake of low-palatable food d High-fat dense food but not sweetened food attenuates the defense against weight gain

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Experimental overfeeding studies have also investigated how diets with different fat content affect energy balance [ 55 , 114 , 156 , 157 ]. One study in male C57BL/6 mice showed that overfeeding with a high-fat diet (40.1% of total calories) or an isocaloric low-fat diet (8.6% of total calories) for six weeks caused a similar weight gain [ 156 ].…”
Section: Lessons Learned From Experimental Overfeeding Studies In Ani...mentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental overfeeding studies have also investigated how diets with different fat content affect energy balance [ 55 , 114 , 156 , 157 ]. One study in male C57BL/6 mice showed that overfeeding with a high-fat diet (40.1% of total calories) or an isocaloric low-fat diet (8.6% of total calories) for six weeks caused a similar weight gain [ 156 ].…”
Section: Lessons Learned From Experimental Overfeeding Studies In Ani...mentioning
confidence: 99%
“…On the other hand, these data also indicate that dietary lipid composition does not modulate the body weight gain that is observed in response to overfeeding. However, this latter notion has recently been challenged by an overfeeding study in which intragastric infusion of a highly palatable high-fat liquid diet weakened the defense against weight gain and increased the voluntary intake of a less palatable low-fat diet in male C57BL/6 mice [ 157 ]. This novel finding is consistent with the idea that diets with high fat content promote the development of obesity [ 158 ] and suggests that the obesogenic effect of dietary fat might, at least partly, be attributed to its ability to impair the still unknown physiological mechanisms that protect against an excessive body weight gain.…”
Section: Lessons Learned From Experimental Overfeeding Studies In Ani...mentioning
confidence: 99%
“…A hypercaloric diet based on carbohydrates has low palatability, so the animals may reduce their body mass instead of increasing it, since animals in nature, once satiated, do not ingest more. On the contrary, a hyperlipidemic diet has better palatability and animals consume it better, thus increasing their body mass [49,50]. Due to the soft texture of the new diets used in this study, wooden blocks were placed in the cages so that the teeth of the mice would wear out and the animals could express their appropriate behaviour.…”
Section: Animals and Experimental Designmentioning
confidence: 99%
“…Additionally, several other studies have not found reduced body weight on dark‐phase TRF [75, 81–83]. However, short length of intervention, rats versus mice, and diet composition could account for the differing results (Table 1), as diets of differing fat content have been shown to affect food intake and body weight [84, 85].…”
Section: Energy Balance Under Active‐phase Trf On Hfdmentioning
confidence: 99%